Determinants of Adherence to Antiretroviral Therapy among HIV-Positive Women Accessing Prevention of Mother to Child Transmission Services in Ebonyi State, Nigeria (2018)
Background: Mother-to-child transmission (MTCT) of HIV accounts for over 90% of all pediatrics infection globally. Strict adherence to antiretroviral drugs is needed to achieve maximal reduction of HIV transmission in pregnancy. Objective: To determine the level of adherence among HIV infected pregnant women on Prevention of Mother to Child Transmission. (PMTCT) antiretroviral therapy and to establish the factors that contribute to poor adherence. Methods: A cross sectional study was conducted in which 268 HIV positive pregnant women were recruited by systematic sampling method from PMTCT clinic of Federal Teaching Hospital Abakaliki. Pre tested interviewer administered questionnaire was used for data collection. Information on socio-demographic characteristics, knowledge of PMTCT, barriers to PMTCT and obstetric characteristics were obtained. Knowledge on PMTCT was accessed and a score of <4 out of 5 indicated poor knowledge. Adherence Level was calculated using the respondent self-report using (3 day recall) and a value < 95% indicated poor adherence. Data were analyzed using descriptive statistics, Chi square and logistic regression (p ≤ 0.05). Results: The mean age was 30.7 ± 4.2 years. Two hundred and nineteen (81.7%) of the respondents were married, 124 (46.3%) were traders and 141 (52.6%) had secondary education. The prevalence of good adherence was 89.2% and 227 (89.0%) had good knowledge of PMTCT. Fear of being identified as HIV positive (21%) pregnancy related illness (13.7%) and forgetfulness (12.5%) were the most common reasons for non-adherence. Partner’s support (OR=.03, 95% CI=0.01-0.09, p=0.001), and duration of ART (OR=4.39, 95% CI=1.3-14.5, p=0.019) at bivariate analysis were found to be significantly associated with good adherence. Partners support (OR=0.027, 95%CI=0.01-0.09) retained the association with good adherence after controlling for cofounders. Conclusion: The study identified that stigmatization and pregnancy related illnesses were related to poor adherence while having Partners support improve adherence to HAART